Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41746-021-00494-5
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing electronic health records to study emerging environmental disasters: a proof of concept with perfluoroalkyl substances (PFAS)

Abstract: Environmental disasters are anthropogenic catastrophic events that affect health. Famous disasters include the Seveso disaster and the Fukushima-Daiichi nuclear meltdown, which had disastrous health consequences. Traditional methods for studying environmental disasters are costly and time-intensive. We propose the use of electronic health records (EHR) and informatics methods to study the health effects of emergent environmental disasters in a cost-effective manner. An emergent environmental disaster is exposu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…This binary classification approach mirrors that taken by previous analyses of PFAS using electronic health records. 27 Although testing for the UCMR3 (2013–2015) occurred toward the end of our study period, the long half-lives of PFAS chemicals suggests that historical concentrations were if anything higher in the past.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…This binary classification approach mirrors that taken by previous analyses of PFAS using electronic health records. 27 Although testing for the UCMR3 (2013–2015) occurred toward the end of our study period, the long half-lives of PFAS chemicals suggests that historical concentrations were if anything higher in the past.…”
Section: Methodsmentioning
confidence: 86%
“…Thus, our study provides significant improvements though both studies were able to replicate several previously observed associations. 27 In this study, we examined a random sample of individuals; however, they are still all hospital patients and thus are more likely to be older and have pre-existing health conditions than the general population. Despite this, associations observed here match associations seen in other large, population-based epidemiologic studies highlighting the generalizability of PFAS health effects and the potential utility of EHRs for PFAS studies.…”
Section: Discussionmentioning
confidence: 99%
“…These algorithms are designed to estimate a patient's risk of developing a particular phenotype or requiring a specific type of clinical care. Some recent applications of predictive algorithms include preterm birth [36], mortality of preterm infants [37], cardiovascular events [38], COVID-19 outcomes [39], critical illness [40], impact of environmental disasters [41], acute kidney injury [42], length of hospital stay [42], 30-day hospital readmission [43], retention of care [44], and postoperative in-hospital mortality [45]. Two important considerations described in these studies are interpretability and transportability.…”
Section: Disease Predictionmentioning
confidence: 99%